Value of Diffusion-Weighted MR Imaging for the Detection of Nephritis - Benjamin Henninger; Miriam Reichert; Stefan Haneder; Stefan O. Schoenberg; Henrik J. Michaely (The Scientific World Journal)
Purpose. To evaluate diffusion-weighted MR imaging (DWI-MRI) for the detection and assessment of infectious renal disease. Materials and Methods. Twenty-one patients with suspicious increased signal intensity of the kidneys on DWI sequences and corresponding ADC decrease were identified. Sixty patients without clinical signs of renal infection served as a control group. All patients were examined with the following sequences: EPI-DWI (0/400/800 s/mm2), T2w HASTE, and T1w VIBE after intravenous injection of Gd-chelate. Confirmation of renal infection was established on the basis of clinical criteria. T1w and T2w images were assessed and compared to DWI for the presence of altered signal, and the degree of the visibility of pathology was graded on an ordinal three-point scale. Results. In all 21 patients with positive DWI findings a renal infection could be confirmed. T2w imaging and contrast-enhanced T1w imaging displayed obvious pathologic signal in 3/21 (14%) and 11/19 (58%) patients and slightly pathologic signal in 17/21 (81%) and 7/19 (37%), respectively. The median visibility score of 2 for the DWI and the T1w images was significantly higher than the score of 1 for the T2w imaging, (DWI versus T2w) and (T1w versus T2w). Conclusion. DWI of the kidneys seems to be highly sensitive for the detection of infections within the kidney.